Fibrinogen function achieved through multiple covalent states - Diego Butera (Nature Portfolio, 2020)
Disulfide bonds play critical roles in determining protein structure and function. Here, the authors show that fibrinogen exists in multiple disulfide-bonded states in human blood, and that these states change during fibrin polymerization and in response to fluid shear forces.